Processing of Noodle Sticks with The Addition of Catfish Meat Flour (Clarias Sp.) - Adi, Catur Pramono; Panjaitan, Pola Sabar Tumohom; Permadi, Aef; Agustin, Anis (Politeknik Kelautan dan Perikanan Karawang, 2022)
The processing of this stick noodle with the addition of catfish flour aims to provide innovation and fortification of fisheries, increase the nutritional content, especially protein and the utilization of nutritious raw materials from fishery commodities, so that people can enjoy snacks with added nutritional value that is good for the body. The objectives of this study were: 1. Making catfish stick noodles from raw materials to the final product, and 2. Knowing the quality characteristics of catfish sticks with the addition of catfish flour. The results showed that: a. The process of processing stick noodles with the addition of catfish flour (Clarias Sp) with the following process flow: Making catfish meal (Weighing, Washing I, Weeding, Washing II, Separating meat, Leaching or washing in cold water 4˚C ± 5 minutes with water ratio 1:4 (2-3 times until clean from fat and blood), Squeezing, Steaming (80˚C ± 20 minutes), Baking (temperature 60˚C 10 hours), Milling and Filtering (blender until smooth 2-3 times) and preparation of ingredients (wheat flour, sago flour, catfish meat flour, eggs, salt and water), kneading (dough until smooth), dough formation (dough in sheet form using a roller machine until thin and evenly distributed, then in the shape of noodles using noodle printing machine), Drying (using an oven 50˚C ± 20 minutes), Frying (using low heat), b. The best formulation for making stick noodles with the addition of catfish flour with a percentage of flour. The catfish is 5% with an average of 6.6 which means it likes sample A5 quite a bit.